KERAGAMAN SPESIES BURUNG PADA VEGETASI ALAMI DI KAWASAN HUTAN LINDUNG LIANG ANGGANG – BLOK I, BANJARBARU, INDONESIA - Atikah Wulansari; Mochamad Arief Soendjoto; Suyanto Suyanto (Jurnal Sylva Scienteae, 2020)
There was no data yet on bird diversity in natural vegetation of Blok I Liang Anggang Protection Forest Area (KHLLA-1) located in Banjarbaru City, Indonesia. This study aimed to analyze the diversity of diurnal birds in natural vegetation of KHLLA-1. Bird data (species, number of individuals, groupings) were collected through transect method between 06.30-09:00 and 16:00-18:30. for three repetitions or three different days. The status of bird protection was determined based on the Minister of Environment and Forestry Regulation No. 106 of 2018. The diversity index was counted according to the Shannon Wienner index. Thirty-seven species of birds found. Most (81.08%) are birds categorized as non waterbirds and the rest are waterbirds. Most (91.89%) are unprotected birds and the rest are protected birds. The index of diversity of bird species in natural vegetation in KHLLA-1 was 3.09. However, from this index not many things can be concluded, except the value is smaller than 3.61, when the number of individuals of each species is the same.Keywords: bird, diversity; natural vegetation; protected forest